2022
DOI: 10.1111/modl.12752
|View full text |Cite
|
Sign up to set email alerts
|

Accumulating Semiotic Resources for Social Actions: A Case Study of L2 Icelandic in the Wild

Abstract: This study investigates a second language (L2) speaker's use and learning of the Icelandic auxiliary verb aetla (pronounced /aihtla/) in the wild. This analytic focus is motivated by the L2 speaker's (Anna) own orientation to aetla as a learnable. We track Anna's use of aetla in naturally occurring social interaction over time. Anna first learns to use aetla to make requests in service encounters but this does not automatically transfer to other environments, suggesting an intricate relationship between aetla … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 76 publications
1
4
0
1
Order By: Relevance
“…The studies reported here—in particular, those by Theodórsdóttir & Eskildsen (2022, this issue), Hellermann & Thorne (2022, this issue), and Pekarek Doehler & Skogmyr Marian (2022, this issue)—align with earlier work that stresses the value of rewilding language education (Thorne et al., 2021) in the form of pedagogical frameworks and infrastructures that center on L2 learners’ needs and experiences of language use outside the classroom. This addresses “the challenge of how to dynamically integrate formal learning settings with the vibrancy and diversity of linguistic, experiential, and situational contexts out in the world” (Hellermann & Thorne, 2022, this issue, p. 93).…”
Section: Implications For Language Educationsupporting
confidence: 80%
See 2 more Smart Citations
“…The studies reported here—in particular, those by Theodórsdóttir & Eskildsen (2022, this issue), Hellermann & Thorne (2022, this issue), and Pekarek Doehler & Skogmyr Marian (2022, this issue)—align with earlier work that stresses the value of rewilding language education (Thorne et al., 2021) in the form of pedagogical frameworks and infrastructures that center on L2 learners’ needs and experiences of language use outside the classroom. This addresses “the challenge of how to dynamically integrate formal learning settings with the vibrancy and diversity of linguistic, experiential, and situational contexts out in the world” (Hellermann & Thorne, 2022, this issue, p. 93).…”
Section: Implications For Language Educationsupporting
confidence: 80%
“…Waring (2018, 2019), for example, showed how interactional practices for turn‐taking and sequential organization can be approached as teachable objects (see also Wong & Waring, 2010). Teaching materials and pedagogic frameworks do not always capture the variety of pragmatic aspects and interactional functions of linguistic resources, as the studies by Theodórsdóttir & Eskildsen (2022, this issue), and by Pekarek Doehler & Skogmyr Marian (2022, this issue) indicate. As Greer & Nanbu (2022, this issue) show, it is also possible that pedagogical approaches that emphasize written grammar influence L2 speakers’ ability to deploy linguistic resources in locally appropriate ways and give rise to practices related to written texts.…”
Section: Implications For Language Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Theodórsdóttir and Eskildsen (2022, this issue) trace the learning and use of the Icelandic auxiliary verb ætla in one individual's learning of Icelandic in the wild over a 3‐year period. The learner, Anna, originally learned to use ætla in service encounters.…”
Section: Discussion Of the Articlesmentioning
confidence: 99%
“…Theodórsdóttir & Eskildsen (2022, this issue) investigate an L2 speaker's use and learning of the Icelandic auxiliary verb ætla (literally, “to intend”) in the wild. The data show that the L2 speaker learns to use ætla to make requests in service encounters, but does not automatically transport her learning to other environments that call on the use of ætla .…”
Section: The Contributions To This Issuementioning
confidence: 99%